New Products in the Serbian Market With Special Emphasis on Fruit Processing Industry – Fruit Juices and Functional Products - Adžić, Veljko (International Journal of Industrial Engineering and Management, 2011)
In the fruit processing industry, i.e., in the production of fruit juices and nectars on the territory of Serbia, the need for juices, which belong to the group of functional products, has been recognized. The goal of this paper is to show that new functional products from fruit juices group are present in the Serbian market and that they have a noticeable role in the market. The very aim of the research is identifying customers’ needs and market potentials for the new products, as well as defining additional benefits for the customer (functional products) and the guidelines for innovative, developing, productive and marketing solutions in the field of fruit processing. The available data from the latest literature as well as web pages and researches have been used for this purpose. Article history: Received (08 April 2011); Revised (16 May 2011); Accepted (09 July 2011)